The Semiology of Motor Disorders in Autism Spectrum Disorders as Highlighted from a Standardized Neuro-Psychomotor Assessment - Paquet, Aude; Olliac, Bertrand; Bouvard, Manuel-Pierre; Golse, Bernard; Vaivre-Douret, Laurence (Frontiers in Psychology, 2016)
Background: Altered motor performance has been described in Autism Spectrum Disorders (ASD) with disturbances in walking; posture, coordination, or arm movements, but some individuals with ASD show no impairment of motor skills. The neuro-developmental processes that underpin the performance of neuro-psychomotor functions have not been widely explored, nor is it clear whether there are neuro-psychomotor functions specifically affected in ASD. Our objective was to focus on the semiology of motor disorders among children with ASD using a neuro-developmental assessment tool. Method: Thirty-four children with ASD, with or without intellectual deficit (ID) were recruited in a child psychiatry department and Autism Resource Centers. Initial standard evaluations for diagnosis (psychiatric; psychological; psychomotor) were supplemented by a standardized assessment battery for neuro-developmental psychomotor functions (NP-MOT). Results: The results of some NP-MOT tests differed between children with ASD with ID and those without. However, on the NP-MOT battery, neither of the two groups did well in the bi-manual and finger praxia tests (36 and 52% respectively failed). Manual and digital gnosopraxia showed some deficit (63 and 62% respectively failed). Postural deficits were found in tests for both static equilibrium (64%) and dynamic (52%). There were also difficulties in coordination between the upper and lower limbs in 58% of children. We found 75% failure in motor skills on the M-ABC test. Concerning muscular tone, significant laxity was observed in distal parts of the body (feet and hands), but hypertonia was observed in the proximal muscles of the lower limbs (reduced heel-ear angle). Discussion: The results of manual and digital gnosopraxia tests point to a planning deficit in children with autism. A gesture programming deficit is also highlighted by the poor results in manual praxis, and by failures in the M-ABC tests despite prior training of the child. However, concerning global motor function, a significant difference was observed between children with and without ID. Our findings suggest a semiology of tone deregulation between proximal versus distal muscles, indeterminate tonic laterality, postural control deficit (proprioceptive), impairment of inter-hemispheric coordination (corpus callosum), and neurological soft signs such asdysdiadochokinesia, which leads us to hypothesize a general impairment of motor functions.